Analisis Performansi Layanan Kluster Server Menggunakan Penyeimbang Beban dan Virtual Box - Fajar Zuhroni; Adian Fatchur Rochim; Eko Didik Widianto (Jurnal Teknologi dan Sistem Komputer, 2015)
Today, the growth of technology is very fast causes people more familiar with the Internet. Web servers are required to more quickly in order to serve a number of user request. Technology uses a single server is underprivileged to handle the load on the web server traffic as the number of users increases, causing the server to fail in serving the request. Technology on cluster server with load balancer is used in order to divide the load evenly so that optimize performance on a web server. Server cluster systems that are designed using six virtual machines using VirtualBox application. Six virtual machine consists of two load balancer servers, two application servers and two database servers. Definition of the system created by outlining system requirements and network topology. System design describes requirements specification of the hardware and software. Analysis and testing conducted to determine the performance of the system designed. Analysis and testing conducted to determine the performance of the system designed. Results of this research is the design of virtual servers that can serve a number of user request. Test result showed maximum ability to serve when all servers are up reach 240 connection, one of the aplication server down is 180 connection and one of the database down is 220.The optimal result when all servers up is 180 connections, one of the aplication server down is 150 connections and when database server down is 160 connections.